2016
DOI: 10.1002/ijgo.12029
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Association of biochemical markers with the severity of pre‐eclampsia

Abstract: The levels of C-reactive protein, blood urea nitrogen, serum uric acid, and alanine transaminase, and the platelet count were linked with the presence and severity of pre-eclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 16 publications
4
14
0
Order By: Relevance
“…This is in agreement with Maged et al 2016 study that showed significant difference between women with severe preeclampsia and women in the other two groups (mild and control) in terms of maternal complications such as HELLP syndrome and eclampsia. Also, this is in agreement with Singh et al 2016 study that showed that HELLP syndrome was the most common maternal complication seen in patients with preeclampsia, whereas pulmonary edema was seen in 3.6% of patients and maternal mortality rate was 1.8% [26,27] .…”
Section: Discussionsupporting
confidence: 91%
“…This is in agreement with Maged et al 2016 study that showed significant difference between women with severe preeclampsia and women in the other two groups (mild and control) in terms of maternal complications such as HELLP syndrome and eclampsia. Also, this is in agreement with Singh et al 2016 study that showed that HELLP syndrome was the most common maternal complication seen in patients with preeclampsia, whereas pulmonary edema was seen in 3.6% of patients and maternal mortality rate was 1.8% [26,27] .…”
Section: Discussionsupporting
confidence: 91%
“…A total of 60 pregnant women at 26–38 weeks of gestation, with pregnancies complicated by severe preeclampsia (29 women with early-onset preeclampsia and 31 women with late-onset preeclampsia) and 65 pregnant women with normotensive, uncomplicated third-trimester pregnancies were included in the study. Blood pressure had been measured on each pregnant patient's arm supported and positioned at the level of her heart on two occasions at least 4 hours apart, with using the first Korotkoff sound for evaluation of the systolic blood pressure and the fifth for assessment of the diastolic blood pressure [ 1 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although there have been extensive studies of preeclampsia, its aetiology remains unclear [ 1 6 ]. However, it is widely accepted that shallow placentation and impaired spiral arteries precede an increase in secretion of antiangiogenic factors and endothelial cells dysfunction, which are underlying mechanisms of preeclampsia [ 2 4 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…MMP-9 is the only effective hydrolase secreted by trophoblast cells that can digest ECM. It has been reported to be involved in extracellular matrix (ECM) remodeling and processes of placental angiogenesis with structural spiral arteries transformation, which precedes proper trophoblastic invasion (10). TIMP-1 is a tissue inhibitory factor corresponding to MMP-9 and is normally secreted by the same kind of cells that secrete MMP-9.…”
Section: Discussionmentioning
confidence: 99%